2017
DOI: 10.1002/adhm.201701036
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Biotechnology Applications of Aqueous Two‐Phase Systems

Abstract: Liquid–liquid phase separation between aqueous solutions containing two incompatible polymers, a polymer and a salt, or a polymer and a surfactant, has been exploited for a wide variety of biotechnology applications throughout the years. While many applications for aqueous two‐phase systems fall within the realm of separation science, the ability to partition many different materials within these systems, coupled with recent advances in materials science and liquid handling, has allowed bioengineers to imagine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 182 publications
(387 reference statements)
0
76
0
1
Order By: Relevance
“…Teixeira et al 109 and Pereira et al 110 compared and discussed novel ATPS-based pattern bioprinting techniques, emphasizing their potential for three major aspects of (i) cell analysis, (ii) cell assembly and cell co-culture, and (iii) bacterial co-culture system.…”
Section: New Trends Of Using Atps In Spheroid Applicationmentioning
confidence: 99%
“…Teixeira et al 109 and Pereira et al 110 compared and discussed novel ATPS-based pattern bioprinting techniques, emphasizing their potential for three major aspects of (i) cell analysis, (ii) cell assembly and cell co-culture, and (iii) bacterial co-culture system.…”
Section: New Trends Of Using Atps In Spheroid Applicationmentioning
confidence: 99%
“…The interfacial tension between the PEGDA-rich phase (P-R) and the DEX-rich phase (D-R) is too small to be measured, and the range is between 0.0001 and 0.1 mN m À1 . 27,40 The interfacial tension (g P/C ) between the PEGDA with the continuous phase (C) decreases and the interfacial tension (g E/C ) between the ETPTA and the continuous phase increases while the PEGDA content increases. Besides, the interfacial tension (g D/C ) between the DEX aqueous solution and the continuous phase decreases with the increasing DEX content.…”
Section: Mechanism Analysis Of Morphology Based On Interfacial Tensionsmentioning
confidence: 99%
“…The aqueous two-phase system (ATPS) consists of two incompatible polymers. 27 When the concentration of a component exceeds a specific value, the solution will spontaneously form two phases. The ATPS can be used to prepare multiple emulsions, 28 microcapsules 29 or particles.…”
Section: Introductionmentioning
confidence: 99%
“…This approach uses an aqueous twophase systems (ATPSs) to confine the cells as they are seeded. ATPSs are composed of two incompatible polymers, or a polymer and a salt, that when dissolved together above threshold concentrations in an aqueous solvent, remain separated by a discrete interface (Albertsson, 1986;Teixeira et al, 2017). Recent work has demonstrated that cells and biomolecules can be confined within ATPSs to support the development of a variety of in vitro cell-based assays (Fang et al, 2012;Frampton, White, Abraham, & Takayama, 2013;Tavana et al, 2009;Tavana, Mosadegh, & Takayama, 2010).…”
Section: Introductionmentioning
confidence: 99%